PROFILING FINANCIAL INCLUSION IN INDONESIA: DOES IT SUPPORT BANK SAVINGS AND HUMAN DEVELOPMENT INDEX? - Supeni Anggraeni Mapuasari; Ahmad Maulin Naufa (Universitas Pakuan, 2022)
ABSTRACTThe purpose of this study was to test its positive correlation on the human development index. This study uses publicly available data from the Indonesian Financial Authority, the Central Statistics Agency, and the World Bank's Global Financial Index Data. Data analysis using correlation analysis. The results showed that the financial inclusion index had a positive correlation with total credit and total savings in each province. It also shows a positive correlation to the provincial-level human development index. The significance of our research is the financial inclusion of the province which brings many benefits to the state to a degree. Therefore, our research is to increase financial inclusion in Indonesia. Financial inclusion research is very limited to provincial-level analysis in emerging markets such as Indonesia, this study aims to expand the literature in this area and fill it.ABSTRAKTujuan penelitian ini bertujuan untuk menguji korelasi positifnya pada indeks pengembangan manusia. Penelitian ini menggunakan data yang tersedia untuk umum dari Otoritas Keuangan Indonesia, Badan Pusat Statistik, dan Data Indeks Keuangan Global Bank Dunia. Analisis data menggunakan menggunakan analisis korelasi. Hasil penelitian menunjukkan indeks inklusi keuangan memiliki korelasi positif terhadap total kredit dan total tabungan di setiap provinsi. Ini juga menunjukkan korelasi positif terhadap indeks pembangunan manusia tingkat provinsi. Signifikansi penelitian kami adalah inklusi keuangan membawa banyak manfaat bagi negara hingga tingkat provinsi. Oleh karena itu, implikasi dari penelitian kami adalah untuk meningkatkan inklusi keuangan di Indonesia. Penelitian inklusi keuangan sangat terbatas pada analisis tingkat provinsi di pasar negara berkembang seperti Indonesia, penelitian ini bertujuan untuk memperluas literatur di bidang ini dan untuk mengisi kesenjangan tersebut.